Spiritualitas Pairan: Konstruksi Teologi Lokal Manusia Baru Konteks Mamasa dalam Dialektika Pairan dan Kolose 2:16-4:1 - Saputra, Jefri Andri (Tumou Tou, 2023)
“Spiritual Pairan” is a writing that aims to construct a new human theology in the context of Mamasa. This research starts from the problem of reducing cultural identity in the post-evangelism church conducted by Geleijnse. In addition, Aluk Mappurondo adherents claim to be "more Christian" than adherents of Christianity which is indicated by their more devout way of religion than adherents of Christianity. Responding to this problem, the author analyzes the text of Colossians 2:16-4:1 and the concept of pairan, to construct a contextual new human in Mamasa. The approach used by the author is a local theological approach. The author hopes that this approach can construct a new human concept that is contextual in Mamasa, so that the churches in Mamasa can show a quality of life that respects culture and displays ethical quality in their lives. After conducting the analysis, the writer finds that the new human construction in the Mamasa context is pairan spirituality. The author recommends that research on the encounter of each component in pairan with Christian traditions can be followed up, such as pairan dapo' with Christian families and pairan lembä with Christian leadership.